A systematic review of the key indicators for assessing telehomecare cost-effectiveness. (2008)
Telehomecare is considered one of the most successful applications of telehealth. However, despite increasing evidence of telehomecare benefits, the diffusion of these services is still limited. Decision-makers need strong evidence in order to expand the development of telehomecare to various populations, regions, and health conditions. The objective of this review is to provide a basis for decision-making by identifying common indicators from the literature on telehomecare. A comprehensive review of the literature on the cost-effectiveness of telehomecare was conducted in specialized bibliographic databases. A total of 23 studies met the inclusion criteria. First, selected studies were analyzed to identify and classify the indicators that better addressed the cost-effectiveness impacts of telehomecare projects. Then, a synthesis of the evidence was done by exploring the relative cost-effectiveness of telehomecare applications. The analyses show that there is fair evidence of cost-effectiveness for many telehomecare applications. However, the heterogeneity among cost-effectiveness indicators in the applications reviewed and the methodological limitations of the studies impede the possibility of generalizing the findings.